Safety and Effectiveness of Electrical and Pharmacological Cardioversion in Persistent Atrial Fibrillation. Part 2: Assessment of Safety - N. Yu. Mironov; V. V. Vlodzyanovskiy; Yu. A. Yuricheva; S. F. Sokolov; S. P. Golitsyn; L. V. Rosenstraukh; E. I. Chazov (Столичная издательская компания, 2019)
Aim. To compare safety of new class III antiarrhythmic drug Refralon with direct current cardioversion (DCC) in patients with persistent atrial fibrillation (AF). Material and methods. 60 patients with persistent AF were randomized to groups of DCC (n=30) and pharmacologic conversion (PCV; n=30). There were no significant differences in age, sex, AF duration, concomitant cardiovascular diseases, CHA2DS2-VASc score and echocardiographic parameters between the groups compared. Initial assessment excluded contraindications to restore sinus rhythm (SR). In DCC group two attempts using biphasic synchronized shocks of 150 J and 170 J were performed. In PCV group patients received up to three subsequent intravenous injections of Refralon 10 μg/kg (maximal dose 30 μg/kg). Results. There were no mortality, stroke, transient ischemic attack, ventricular arrhythmia, asystole longer than 3,0 sec (primary safety criteria) in both groups. Prolongation of QT interval longer than 500 ms observed in 1 of 30 patients (3,3%) in DCC group and in 7 of 30 patients (23,3%) in PCV group. 2 patients (one patient in each group; 3,3%) developed asymptomatic bradycardia after conversion to SR that resolved spontaneously within 30 minutes. 95% confidence interval (95%CI) for secondary safety criteria is [0,02-0,38] for QT prolongation and [-0,04-0,04] for bradycardia. Conclusion. Safety of PCV is noninferior to DCC in patients with persistent AF in terms of primary safety criteria and bradyarrhythmias. More frequent QT interval prolongation to values >500 ms observed in PCV group points to necessity of precautions with use of the drug.